2014
DOI: 10.7863/ultra.33.8.1407
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time Sonographically Guided Percutaneous Dilatational Tracheostomy Using a Long‐Axis Approach Compared to the Landmark Technique

Abstract: Percutaneous dilatational tracheostomy under real-time sonographic guidance using a long-axis approach may increase the rate of midline punctures and decrease the number of needle punctures when compared to the landmark technique. Sonographic guidance can also help guide accurate and efficient placement of a tracheostomy tube into the desired tracheal ring space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
(60 reference statements)
1
27
0
1
Order By: Relevance
“…The patient is now given fentanyl for pain, midazolam for sedation and rocuronium for paralysis. Then after optimally positioning the patient, scrubbing in and preparing a sterile field, an US is used to scan the anterior neck and identify a site for safe needle insertion [28][29][30][31][32][33][34][35][36][37][38][39]. The needle is then inserted (Fig 2 A1) using real-time US guidance.…”
Section: The Modified Pdt Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…The patient is now given fentanyl for pain, midazolam for sedation and rocuronium for paralysis. Then after optimally positioning the patient, scrubbing in and preparing a sterile field, an US is used to scan the anterior neck and identify a site for safe needle insertion [28][29][30][31][32][33][34][35][36][37][38][39]. The needle is then inserted (Fig 2 A1) using real-time US guidance.…”
Section: The Modified Pdt Techniquementioning
confidence: 99%
“…Recently, real-time US guidance [33][34][35][36][37][38][39][40] has been used as a substitute for bronchoscopy during placement of the needle and guide-wire. When using the US for PDT, current techniques still begin with positioning of the ETT just below the level of the vocal cords either under DL or US guidance [37,38].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it was stated that the use of USG decreases the number of tracheal punctures and enables the procedure to be performed more safely and easily. In another study examining the use of USG during bronchoscope-guided PT, it was specified that USG increases the rate of midline tracheal puncture, decreases the number of tracheal punctures, and allows a tracheostomy cannula to be located between the targeted tracheal rings (23). In a study evaluating the use of USG during multiple dilatation method, no difference was found in terms of minor bleeding, needle puncture place, and the number of punctures when USG was used, even without a bronchoscope.…”
Section: Use Of Usg During Tracheal Puncturementioning
confidence: 99%
“…Por outro lado, a ultrassonografia e a broncoscopia não são mutuamente excludentes, e podem ser utilizadas em combinação para aumentar a eficácia e a segurança da traqueostomia percutânea [35][36][37] . A traqueostomia percutânea guiada por ultrassonografia pode ainda ser utilizada como uma alternativa à traqueostomia percutânea guiada por broncoscopia, especialmente, em cenários nos quais a broncoscopia não se encontra amplamente disponível.…”
Section: Gráfico 1 -Gráficos De Não Inferioridadeunclassified